Meningkatkan Kemampuan Struktur Jembatan dengan Sistem Girder Pelat Baja pada Jembatan Golo, Tumpakoyot Blitar - Muhammad Yusuf Ansori; Edy Gardjito; Sigit Winarto; Fajar Romadhon; Haris Wicaksono (Faculty of Engineering, Kadiri University, 2021)
The bridge becomes a vital building in living today, which is connecting two areas that separated land. The Golo Bridge also connects the two regions, Blitar and Tulungagung. The Golo Bridge in Tumpakoyot Blitar is part of a national project to build alternative and fast routes in the Southern Java alternative route. The existing Golo bridge is a bridge with a PC-I Girder structure 40 m long and 11 m wide. This research aims tore-plan or modify it to become a bridge with a steel plate girder structure by dividing it into 2 spans, collecting the existing data to be processed in the analysis calculation. It's started with determining the dimensions of the initial structure, giving loads, controlling the structure's ability, also for the abutment & pier. The calculation shows that the dimensions of the steel plate girder have a profile of 2500. 700. 14. 40 mm. Meanwhile, the abutment has a total height of 5.70 m, a width of 4.50 m, and 9.50 m. The bridge pillars have a total height of 6.20 m, a width of 6.20 m and a length of 9.50 m. These results show that the structures is able to support the working loads.